Persepsi kemudahan, manfaat, harga dan kualitas produk terhadap keputusan belanja: peran moderasi kepercayaan pelanggan - Koerniawan Hidajat; Rezky Agung Setiawan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
The purpose of this study was to analyze the effect of perceived ease of use, perceived usefulness, perceived price and product quality on shopping decisions with customer trust as a moderating variable. The sample is 120 consumers of the Cumart digital application in the North Jakarta area. Data were analyzed using PLS-SEM. The research findings show that there is no significant effect of perceived ease of use, perceived usefulness, and perceived price on shopping decisions, but product quality and customer trust have an effect on shopping decisions. Customer trust is not able to moderate perceptions of ease of use, usefulness, price, and product quality on shopping decisions. Further research is still needed regarding perceived ease of use, perceived usefulness, and perceived price, which can be related to customer satisfaction with using online-based shopping applications.